Peracetic acid fate and decomposition in poultry processing wastewater streams. (September 2019) - Chen, Jinchen; Pavlostathis, Spyros G.
Abstract: Peracetic acid (PAA) has been increasingly used by the poultry processing industry. However, information related to the potential PAA carryover to and effect on biological treatment processes, commonly used in poultry processing wastewater treatment, is limited. The objectives of this work were to assess the fate of PAA in poultry processing wastewater streams, investigate dominant factors contributing to PAA decomposition, and identify major PAA decomposition products. PAA was detected in chiller overflow and in the dissolved air flotation (DAF) unit influent and effluent only at the end of the processing shift. The PAA decomposition rate correlated positively with pH, temperature, wastewater strength and organic content, and negatively with initial PAA concentration. PAA decomposition followed one-step (pH ≥ 6) or two-step (pH < 6) pseudo-first order kinetics. Decomposed PAA in DAF effluent resulted in equimolar production of acetic acid. A decrease in DAF effluent COD was observed under high PAA doses. Highlights: Peracetic acid (PAA) carryover to DAF unit detected at the end of operation shift PAA decomposition follows first-order kinetics in poultry waste streams (pH ≥ 6). The rate of PAA decomposition in poultry waste streams is primarily affected by pH. Protein is the major wastewater component affecting the rate of PAA decomposition. PAA decomposition resulted in equimolar acetic acid production